Diplomado de Análisis y Diseño de Estructuras: Módulo Optativo (STAAD PRO Avanzado) - Monroy Miranda, Fernando (My University, 2005)
STAAD PRO the next level of STAAD III is the leading Structural Analysis and Design software from Research Engineers. In STAAD/ Pro the focus is on productivity, STAAD/Pro addresses the entire process of Structural Engineering from model development to analysis to design to drafting to detailing –and even component design- STAAD/Pro is designed to work the way the Structural Design office works.
Keywords: Staad pro avanzado; Type of structures, coordinate systems, solid elements, material constants, suports, loads, stiffness analysis, dynamic analysis, member and forces, memeber properties, stress, weld design, concrete design, beam design, column design, slab/wall design, timber design, commands, wind load, natural frequency, load combination, problem statistics, concrete, beam element, stardyne, node